Reconsidering People as the Institution: Empathy, Pay Equity, and Deaccessioning as Key Leadership Strategies in Art Museums. (1st May 2021) - Whitaker, Amy
Abstract: Drawing on recent research in empathy, pay equity, and deaccessioning practice in U.S. art museums, this paper argues for a creative reconsideration of art museums by reframing the institutions not in terms of their buildings or their collections but their people. The coronavirus pandemic has offered a break in art museums' physical stories and called into sharp relief managerial trade‐offs between support of staff and sale of objects. By focusing on empathy, pay equity, and deaccessioning strategies, art museum leaders can imaginatively and analytically renew the social contract between art museums and their workforces and audiences, creating new structures of pay equity and firmer financial footing and more robust community governance in order to weather future challenges with equanimity and focus. By focusing on empathy and equity, museums also build their own resilience instead of risking closure for financial reasons without public trust to fall back on.